Retrospective Analysis of Molecular Markers in Endometrial Cancer: Single Center Experience - Cem Yagmur Ozdemir; Dagistan Tolga Arioz; Nayif Cicekli; Mariam Chkhikvadze; Filiz Bilir; Cigdem Ozdemir; Hacer Demir; Evrim Suna Arıkan Soylemez (IMR Press, 2024)
Background: To emphasize the effect of molecular markers on prognosis in endometrial cancer, in addition to the International Federation of Gynecology and Obstetrics (FIGO) 2009 classification. Methods: The records of 160 patients with endometrial cancer between 2008 and 2022 were retrospectively reviewed. Staging was done according to FIGO 2009 criteria. Patients were divided into 4 groups according to molecular classification. If one had polymerase epsilon (POLE) mutation, the patient was included in POLE ultramutated (POLEmut) group. In case of intakt POLE, but abnormal staining of mismatch repair (MMR), the group was diagnosed as mismatch repair defciency (MMRd). If there was only p53 abnormal results detected, that group was p53-abnormal (p53mut). If no mutation at all, that group was categorized as non-specific molecular profile (NSMP). The Kaplan-Meier method was used to evaluate overall survival and progression-free survival. Survival rates were compared for molecular markers. Results: According to the molecular analysis, 4 patients (2.5%) were classifed as POLEmut group, 53 patients (33.1%) in the MMRd group, 18 patients (11.3%) had p53mut, and 85 patients (53.1%) into the NSMP group. 5-year overall survival was 79.4%, 5-year progression-free survival was 90%. 5-year overall survival was 75% in POLEmut group, 84.9% in MMRd group, 38.9% in p53mut group and 84.7% in NSMP group (p = 0.001). 5-year progression-free survival was 100% in POLEmut group, 96.2% in MMRd group, 77.8% in p53mut group and 88.2% in NSMP group (p = 0.082). Conclusion: Our study shows the prognostic value of the molecular endometrial cancer classification. Patients with p53mut have a poor progression-free survival, POLEmut endometrial cancer have a good prognosis. In this study, we wanted to demonstrate the importance of molecular markers in endometrium cancer and their contribution to prognosis.